In school or at work? Evidence from a crisis - Florencia López Bóo (Institute for the Study of Labor (IZA), 2010)
This paper examines the effect of labor market opportunities on schooling-employment decisions in 12 urban areas in Argentina over 12 years, emphasizing the recession/crisis years 1998-2002. The effects of macroeconomic swings on schooling decisions are examined with a focus on whether the income or substitution effect dominates as macroeconomic conditions change. I demonstrate that over typical years deteriorating job rates (or wages) increase the probability of attending school and decrease the probability of combining work and school, particularly for boys. After controlling for household and individual characteristics I find that the probability of being in school for secondary school youth was about 6 percentage points higher in 2002 than in 1998 (before the recession started). In fact, a 10 percent decrease in the job rate alone has been responsible for a 5.4 percentage point rise in the probability of school attendance since 2000. This effect is attenuated during the 2002 crisis when household expectations change in response to shocks. These estimates allow for the fact that a new Federal Education Law (FEL) in 1996 extended mandatory education to 10 years and might have affected schooling outcomes.
Keywords: I21; J31; 330; Schooling decision; macroeconomic shocks; local labor market opportunities; Bildungsverhalten; Regionaler Arbeitsmarkt; Schock; Regionaler Konjunkturzyklus; Argentinien